Investigating the effect of reduced temperatures on the efficacy of rhabdovirus-based viral vector platforms - Kakish, Julia E.; Mehrani, Yeganeh; Kodeeswaran, Arthane; Geronimo, Katrina; Clark, Mary Ellen; van Vloten, Jacob P.; Karimi, Khalil; Mallard, Bonnie A.; Meng, Baozhong; Bridle, Byram W.; Knapp, Jason P. (Journal of general virology, 2024)
Rhabdoviral vectors can induce lysis of cancer cells. While studied almost exclusively at 37 °C, viruses are subject to a range of temperatures in vivo , including temperatures ≤31 °C. Despite potential implications, the effect of temperatures <37 °C on the performance of rhabdoviral vectors is unknown. We investigated the effect of low anatomical temperatures on two rhabdoviruses, vesicular stomatitis virus (VSV) and Maraba virus (MG1). Using a metabolic resazurin assay, VSV- and MG1-mediated oncolysis was characterized in a panel of cell lines at 28, 31, 34 and 37 °C. The oncolytic ability of both viruses was hindered at 31 and 28 °C. Cold adaptation of both viruses was attempted as a mitigation strategy. Viruses were serially passaged at decreasing temperatures in an attempt to induce mutations. Unfortunately, the cold-adaptation strategies failed to potentiate the oncolytic activity of the viruses at temperatures <37 °C. Interestingly, we discovered that viral replication was unaffected at low temperatures despite the abrogation of oncolytic activity. In contrast, the proliferation of cancer cells was reduced at low temperatures. Equivalent oncolytic effects could be achieved if cells at low temperatures were treated with viruses for longer times. This suggests that rhabdovirus-mediated oncolysis could be compromised at low temperatures in vivo where therapeutic windows are limited.